Country index for family businesses: Competitiveness ranking, 8th edition summary - Verena K. Dutt; Leonie Fischer; Fynn Minkus; Margit Kraus (Stiftung Familienunternehmen, 2021)
This update of the Country Index for Family Businesses evaluates Germany's attractiveness as a location for family businesses for the eighth time since 2006. Our index compares industrialized countries in terms of their attractiveness as locations for business investment. While we focus on conditions prior to the Coronavirus pandemic, our analysis sheds important light on the extent to which various European and non-European countries will be in a position to ward off the long-term effects of the pandemic. For the first time the 2020 index includes a comparative analysis of healthcare systems. The full German version of the Country Index for Family Businesses has been published by the Foundation for Family Businesses. The English text presented here summarizes the main findings of the original version.
Keywords: 330